A Re-appraisal of the King's Ships in the Reigns of Richard I and John, 1189–1216. Issue 1 (2nd January 2020) - Rose, Susan
Abstract : Claims have been made for the establishment of an English royal navy in the twelfth century. This article offers a reappraisal of the documentary evidence to assess whether Richard the Lionheart or his younger brother John can be credited with creating this instrument of royal power. Their use of ships in warfare and the possession of vessels by the Crown was very similar. A small group of ships owned by the king was quite common, but the casual use of the term 'our galleys' by clerks makes it difficult to distinguish these from the more numerous vessels on paid service to the crown. The major purpose of ships in warfare was to provide logistical support. More warlike actions were rare. Neither monarch had the resources or the need for more than a small squadron of ships owned by the crown. The evidence for the establishment of a naval base at Portsmouth is investigated and it is concluded that rather than a permanent dockyard it was simply a secure winter boat yard where the king's vessels could be drawn up out of the water with their rigging safely stored. Technical developments in ship design and weaponry in the course of the sixteenth century and changes in the nature of warfare led to the emergence of what is rightly called the Royal Navy. However if the term is more loosely used for a squadron of vessels in royal ownership, which provided the core of conscripted fleets in actions at sea, it may, perhaps, be justifiably applied as early as the late twelfth century.